2020
DOI: 10.11607/ofph.2641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic Polymorphisms on Pain Sensitivity in the Orofacial Region: A Systematic Review

Abstract: To systematically review the literature to assess whether genetic polymorphisms affect orofacial pain sensitivity in healthy individuals and in patients with chronic orofacial pain disorders. Methods: Electronic searches were conducted to identify observational studies and clinical trials investigating the association between genetic polymorphisms and orofacial pain sensitivity in healthy individuals and/or patients with chronic orofacial pain disorders. Searches were carried out in PubMed, Embase, and Scopus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
11
0
2
Order By: Relevance
“…[28][29][30] These findings indicate that genes related to these mechanisms of modulation of the nociceptive impulse may influence not only the evaluation of somatosensory characteristics, such as mechanical pain sensitivity, but also the temporal summation and descending pain modulation. According to a recent systematic review, 31 only seven studies assessed pain sensitivity in the orofacial region on chronic pain patients using reliable and valid tools, such as quantitative sensory tests. It seems that genetic polymorphisms related to catecholaminergic, inflammatory, opioid, and dopaminergic pathways were associated with sensitivity to thermal and pressure stimuli in the orofacial region, but there is not enough data to firmly support this evidence.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] These findings indicate that genes related to these mechanisms of modulation of the nociceptive impulse may influence not only the evaluation of somatosensory characteristics, such as mechanical pain sensitivity, but also the temporal summation and descending pain modulation. According to a recent systematic review, 31 only seven studies assessed pain sensitivity in the orofacial region on chronic pain patients using reliable and valid tools, such as quantitative sensory tests. It seems that genetic polymorphisms related to catecholaminergic, inflammatory, opioid, and dopaminergic pathways were associated with sensitivity to thermal and pressure stimuli in the orofacial region, but there is not enough data to firmly support this evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of COMT activity is related to increased pain sensitivity and the production of proinflammatory cytokines (Senagore et al, 2017). A recent systematic review showed that genetic polymorphisms of the catecholaminergic pathways are associated with thermal and blunt pressure sensitivity (Soares et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The conditioned pain modulation (CPM) paradigm is a valid and reliable psychophysical approach to evaluate the efficacy of the descending pain inhibition, under the assumption of "pain inhibits pain" that is a phenomenon that has important clinical applications, particularly, because can depict possible pain mechanisms underlying chronic pain conditions (Yarnitsky, 2015;Costa et al, 2017). CPM paradigms have also been reported as a potential tool for additional understanding of pain mechanisms that would improve treatment outcomes and can be held in a sequential form or parallel form (Costa et al, 2017;Soares et al, 2020), and in the present work we used the sequential CPM.…”
Section: Introductionmentioning
confidence: 99%
“…Poucos estudos avaliam a sensibilidade à dor na região orofacial em pacientes com dor crônica usando ferramentas confiáveis e válidas, como testes sensoriais quantitativos, conforme avaliado por uma revisão sistemática recente (SOARES et al, 2020). O estudo OPPERA (Orofacial Pain Prospective Evaluation Risk and Assessment), o maior estudo genético em DTM, analisou 3.295 polimorfismos de 358 genes envolvidos em sistemas relevantes para a percepção da dor em 2.700 indivíduos, além de uma bateria de testes sensoriais (SLADE et al, 2011;SMITH et al, 2013).…”
Section: B Ep B β Valor De P B -95% CIunclassified
“…Além disso, em termos de sensibilidade à dor mecânica, apenas o diagnóstico de DTM foi capaz de influenciar o PPT no músculo masseter, como esperado, uma vez que o próprio diagnóstico de DTM pressupõe maior sensibilidade do masseter (GOMES et al, 2008;HERPICH et al, 2018;PINTO FIAMENGUI et al, 2020;SHARMA et al, 2020;SLADE et al, 2016;SOARES et al, 2020) SESSLE, 1999). Não pudemos observar tal evidência em nossa amostra.…”
Section: B Ep B β Valor De P B -95% CIunclassified